2022
DOI: 10.1029/2021sw002958
|View full text |Cite
|
Sign up to set email alerts
|

COMPASS: A New COnductance Model Based on PFISR And SWARM Satellite Observations

Abstract: Ionospheric height-integrated conductivity (conductance) is a key parameter in the coupling processes among the magnetosphere, the ionosphere, and the thermosphere. It is mainly produced by photoionization on the dayside due to solar radiation and can be altered by auroral precipitation from the magnetosphere and solar wind due to impact ionization. Variations in conductance can in turn influence magnetospheric convection. The increase of conductance can also lead to an expansion of the thermosphere through Jo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Their newly developed model included a full year results of AMIE, and was extended to encompass extreme storm conditions. Wang and Zou (2022) recently reported a statistical conductance model trained from the ground-based PFISR data and in-situ Swarm observations of FACs, providing another option for the community to specify the high-latitude conductance distribution based on FAC information. Studies also suggested that secondary electrons produced by the interaction between precipitating electrons and the neutral atmosphere can reflect multiple times between hemispheres and further contribute to the diffuse aurora (Khazanov et al 2016).…”
Section: Specification Of Ionospheric Conductance In Global Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their newly developed model included a full year results of AMIE, and was extended to encompass extreme storm conditions. Wang and Zou (2022) recently reported a statistical conductance model trained from the ground-based PFISR data and in-situ Swarm observations of FACs, providing another option for the community to specify the high-latitude conductance distribution based on FAC information. Studies also suggested that secondary electrons produced by the interaction between precipitating electrons and the neutral atmosphere can reflect multiple times between hemispheres and further contribute to the diffuse aurora (Khazanov et al 2016).…”
Section: Specification Of Ionospheric Conductance In Global Modelsmentioning
confidence: 99%
“…It is suggested that one is aware of the limitations and advantages of these approaches while applying them. For example, as indicated in Robinson et al (2020) and Wang and Zou (2022), larger FACs under more disturbed conditions are less sampled, calling for cautions when applying these models to severe storms.…”
Section: Specification Of Ionospheric Conductance In Global Modelsmentioning
confidence: 99%
“…Liemohn (2020) reviewed the history, limitations, and alternative solutions for the Robinson formulas. Several efforts have recently been made to improve the specification of ionospheric conductances, including using a large data set to determine the relation between electron precipitating flux and ionospheric conductances (Kaeppler et al, 2015(Kaeppler et al, , 2023McGranaghan et al, 2015), applying optimal interpolation analysis (McGranaghan et al, 2016), or determining the relation between FAC and conductances (Robinson et al, 2020;Z. Wang & Zou, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the input FACs are not identical to the output FACs (calculated from the electric potential and ionospheric conductance) especially on dusk side. Other studies also investigated the relationships between FACs and ionospheric conductance (e.g., Korth et al., 2014; Mukhopadhyay et al., 2020; Ridley et al., 2004; Wang & Zou, 2022). More recently, Chartier et al.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the input FACs are not identical to the output FACs (calculated from the electric potential and ionospheric conductance) especially on dusk side. Other studies also investigated the relationships between FACs and ionospheric conductance (e.g., Korth et al, 2014;Mukhopadhyay et al, 2020;Ridley et al, 2004;Wang & Zou, 2022). More recently, Chartier et al (2022) also used the AMPERE FAC to drive the SAMI3 model (Huba et al, 2008), in which the auroral electron precipitation is specified by an empirical model developed by Hardy et al (1985).…”
mentioning
confidence: 99%